The effect of 900-MHz radiofrequency electromagnetic fields during the adolescence on the histological structure of rat testis and its androgen and estrogen receptors localization - Gur, F. M.; Keles, A. Ikinci; Erol, H. S.; Guven, C.; Taskin, E.; Kaya, H.; Timurkaan, S. (Ijrr-Iranian Journal Radiation Res, 2021)
Background: Mobile phones as an electronic device which are emitting radiofrequency-electromagnetic field (RF-EMF). In this study was intend to determine the contingent effects of cell phone induced RF-EMF on testicular tissue in adolescence. Materials and Methods: Rats in the RF-EMF group were exposed to 900 MHz RF-EMF, while sham and control rats were not. After the completion of the test steps, the testicular tissues which were rapidly removed from the body of sacrificed rats were examined by using histopathological and biochemical methods. Testicular tissues cut to 5 mu m thickness undergo routine histological procedures. Thus, histopathological evaluation will be completed. Malondialdehyde (MDA), glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD) levels in testicular tissues were measured by biochemical methods to determine whether oxidative stress occurred or not. Results: Histopathologic findings were not observed in any of the studied groups. There was also no difference between the groups in terms of localization of androgen and estrogen receptors. The incidence of apoptotic index and TUNEL-positive cells was similar in all three groups. In the RF-EMF group, although the levels of MDA and CAT were significantly higher, GSH levels were lower than the other groups. There was no essential difference between the groups in terms of SOD level. Conclusions: The obtained results of this study showed that exposed to 900 MHz RF-EMF in adolescents caused oxidative stress in the testes, but testicular damage which is caused to oxidative stress is remained too low to be detected by histopathological methods in this study.
Keywords: Androgen receptor; apoptosis; electromagnetic field; estrogen receptor; testis